SCARA Robot Application for Automatic Vending Machine Movement Based on HMI dan IoT - Febrianto, Fauzan; Risfendra (Department of Electrical Engineering Universitas Negeri Padang, 2024)
This design discusses the application of HMI and IoT-based SCARA robots to control and monitor the movement of vending machines. The purpose of this design is to be able to perform programming on the SCARA Robot using the RC-90B Controller and Programmable Logic Controller (PLC), design interface designs for control systems, and monitor system responses using the Human Machine Interface (HMI) and Internet of Things (IoT). As well as testing the functional performance of the SCARA robot and Node-RED. This design is supported by the RC-90B controller, Siemens S7-1200 PLC, Seimens KTP-700 Basic PN HMI, and Node-RED. A series of programming processes and making system interfaces are carried out using Epson RC-7.0 software, TIA Portal, and Node-RED. In this design, a vending machine movement process will be made, namely: pick, place, and assembly materials using vacuum and gripper assistance. In addition, the author also uses the palletizing function in the material preparation process. Then take important data such as robot speed, cycle time, and success rate, where each product is tested and get the best results with a 0% error value